Anka Satira: o naslovu - Plejić, Lahorka (Array, 2006)
Marulić's poem Anka Satira, extant only in Petar Lucić's manuscript collection Vartal, raises numerous questions in its title. This concerns, above all, the word satira. While in the Latin in Marulić's time, and for a long time in Croatian too, the word satire was written with letter y instead of i (satyra), in Italian it was written satira, just as it is in Vartal, and it is assumed that the word in this case is adopted from the Italian. Since the recipients for whom the poem was designed did not know either Latin or the tradition of the Roman satire and the satirical epigram, it must be assumed that the meaning of the word in Marulić's title is wider than is comprised by the term satire today. According to obsolescent interpretations of the satire, it was tightly linked with satirical laughter and mockery. Such interpretations and indeed the graphic form of satyra were produced first of all by false etymology, according to which the satire was linked with the mythological satyr. Such a link between the satire and the satyr was live in Marulić's period. Apart from that, the other member of the phrase of the title is written with a large initial letter, and so the word Satira in the title could be understood primarily as a female form of the noun satyr or as part of female name or nickname, rather than as term from literary studies. But it is still not clear why Anka and Satira should be linked, for she neither takes part in the mockery in the poem or in being mocked. Uncertainties about how the title is to be understood and hesitations in the reception of Anka Satira as satire are reflected in works of scholars who have dealt with the poem, from Slamnig via Fališevac to Lučin. While some read the poem as jocularly satirical, others hardly mention the satirical aspect, which suggests the possibility of differing receptions. Some, then, place the emphasis on the central part of the poem in which the wooers are mocked. To others the meaning that derives from the mockery is more important, i.e., the apologia for the conventual life, addressed to young girls.